Tax expenditures versus direct government spending: A comparative efficiency analysis - Karl-Heinz Paqué (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1984)
Until recently the concept of tax expenditures has been exclusively analyzed along traditional Pigouvian lines. Broadly speaking, the introduction of tax/subsidy-schemes was considered to be justified whenever large number externalities prevent the market from working efficiently. This approach - while fruitful and important in its own right - neglects a fundamental policy problem, namely the public choice option between tax expenditures and direct government spending: independent of any welfare theoretic rationale for public intervention, there remains the question which kind of intervention - tax expenditure (implicit subsidization) or direct expenditure - is the most efficient solution.
Keywords: 330